The Role of Philanthropic Institutions in the Clean Water Distribution Program in Gunungkidul Regency: Peran Lembaga Filantropi Dalam Program Penyaluran Air Bersih di Kabupaten Gunungkidul - Latipah, Lutfi Nur; Saharuddin, Erni (Universitas Muhammadiyah Sidoarjo, 2025)
Drought is a natural disaster that cannot be avoided and occurs annually in Indonesia. Data from National Agency for Disaster Countermeasure for the years 2020-2024 indicates that the number of districts/cities affected by drought has shown both increases and decreases, varying each year. Therefore, efforts from both the government and private sectors are necessary to provide clean water programs for the community. Philanthropic institution, such as LAZISMU, are also involved in addresing this issue. The objective of this study is to analyze the implementation of the clean water program by LAZISMU. The research employed a qualitative study with a descriptive analysis approach. The results indicated that there where obstacles in the implementation of the clean water distribution program, such as a lack of communication among various LAZISMU branches in Special Region of Yogyakarta, which led to overlapping clean water distribution in some areas, and the budget allocation by LAZISMU has not yet been sufficient to meet the needs of the entire community. Structured coordination is needed, such as regular meetings among LAZISMU throughout the Yogyakarta prior to distribution, is necessary to ensure effective, targeted, and equitable clean water distribution